ACADEMIC BURNOUT CONDITIONS IN INDONESIAN STUDENTS: PHYSICAL, MENTAL, AND EMOTIONAL - Supriyanto, Agus; Imtinan, Salsabila; Arikunto, Suharsimi; Handaka, Irvan Budhi; Hartini, Sri (EDUCATIONE, 2024)
The unclear end of the Covid-19 pandemic has had an impact on learning in schools. Students as an affected community cause the online learning process with various limitations, even though students have begun to get used to online learning. Conditions related to online learning pose a new problem about academic burnout. This study aims to develop an academic burnout scale and describe the condition of student academic burnout. The research method uses a mix-method with academic burnout variables and the target is students. The results found three aspects of academic burnout from physical fatigue, mental exhaustion, and emotional exhaustion. The burnout scale is validly tested with reliability in the very high category. The measurement of student academic burnout found that the average student has a high burnout category as a result of online learning. The effects of burnout conditions are self-confidence, motivation, achievement, self-control or depression in students. Immediate intervention for the prevention, reduction, or alleviation of burnout by school counselors or in collaboration with psychologists or universities.